Pengaruh Posisi Cabang Pembuahan terhadap Pertumbuhan, Hasil, dan Mutu Buah Melon (Cucumis melo L.) dalam Sistem Fertigasi Hidroponik - Ikhwana, Muhammad Habib; Susila Putra, Eka Tarwaca; Ambarwati, Erlina (Universitas Gadjah Mada, 2025)
Melon have the potential to produce 10-20 fruits per plant; however, the quality of each fruit is often suboptimal due to inefficient assimilate distribution. This study aimed to determine the optimal fruiting branch position to maximize the growth, yield, and quality of melons in a fertigation hydroponic system. The research was conducted in a 168 m² greenhouse owned by PT Lentera Agropedia Nusantara, located in Pripih, Hargomulyo, Kulon Progo, Special Region of Yogyakarta, Indonesia. A split-plot experimental design was used, with melon cultivars (Sweet Hami and Kirin) as the main factor and fruiting branch positions (lower, middle, and upper) as the sub-factor. The results showed that middle (9th to 10th nodes) and upper (11th to 12th nodes) fruiting branches exhibited greater fruit weight, length, and diameter compared to lower branches (7th to 8th nodes). Kirin cultivar had thicker flesh, and the interaction between cultivar and branch position significantly influenced the fruit cavity diameter. Middle and upper branches produced fruits of similar quality when harvested at 70 days after planting. Fruiting on the lower branches (7th to 8th nodes) produces fruits with lower weight, length, and diameter.Considering the risks associated with fruiting on upper branches, it is recommended to maintain melons on middle branches, specifically at the 9th to 10th nodes.